Dreamweaver CC the missing manual - McFarland, David Sawye; Grover, Chris (O'Reilly Media, 2015)
Dreamweaver CC is a powerful tool for designing all kinds of websites, from those with simple, static pages to interactive, media-driven sites for desktop, laptop, and mobile devices.